Bael (Aegle marmelos L. Corrêa), a Medicinal Tree with Immense Economic Potentials - Chamila Kumari Pathirana; Terrence Madhujith; Janakie Eeswara (Advances in Agriculture)
Bael (Aegle marmelos L. Corrêa) is an economically valuable tree species in South Asia. The ripen bael fruits are popular among people because of the delicious fruit pulp, which is ideal for making jam, syrup, and pudding. Bael possesses many medicinal values and therefore used as an ingredient in ayurvedic herbal medical preparations. The fruits, bark, leaves, seeds, and roots of bael contain bioactive compounds such as coumarin, xanthotoxol, imperatorin, aegeline, and marmeline. These compounds can provide antidiabetic, anticancerous, antifertility, antimicrobial, immunogenic, and insecticidal activities. Bael is also essential as a species for reforestation, especially in the unfertile marginal lands. Bael seeds possess a unique fatty acid (12-hydroxyoctadec-cis-9-enoic acid or ricinoleic acid), a convertible item into biodiesel. Bael is an underutilized fruit species in South Asian countries. However, numerous studies report the medically significant properties and industrially vital characteristics of bael in India. The present review focused on summarizing and discussing the essential details and potentials of bael for industrial applications towards economic development.